Comparison of Flake ice and Gel ice in the Preservation of Lethrinus lentjan (Lacepede, 1802) Fillets - Hassan, Femeena; Joshy, C. G. (Fishery Technology, 2018)
Effectiveness of different icing, gel ice and flake icein extending the shelf life of fish fillets (Lethrinuslentjan) (Lacepède, 1802) was evaluated. Sampleswere taken from preserved samples at two daysintervals for organoleptic, biochemical and microbiologicalanalysis up to 16 days of storage. Basedon t-test, the biochemical variables viz., pH, TotalVolatile Base Nitrogen (TVB-N) and TrimethylamineNitrogen (TMA-N), ThioBarbituric Acid Value (TBA)Free Fatty Acid (FFA) and Peroxide value (PV)showed a significant difference between two methodsof icing at. Organoleptic scores for appearancecolour, odour, texture and overall acceptability weretested. The results revealed that there was nosignificant difference between two methods of icingat 5% level of significance during storage, but thesignificant difference noticed at 10% level ofsignificance. Based on the biochemical and organolepticanalysis, it is inferred that gel icing was betterthan flake ice storage for storage up to 8 days.Simple linear regression model (significant R2 value)to the experimental data of both type of icing toquantify the rate of change which indicated asignificant increase in the quality indices as thestorage days increased. On the other hand the rateof increase of biochemical quality indices wasminimum for samples stored in flake ice.